Promoting research and audit at medical school: evaluating the educational impact of participation in a student-led national collaborative study - Chapman, Stephen J (BMC Med Educ, 2015)
BACKGROUND: Medical students often struggle to engage in extra-curricular research and audit. The Student Audit and Research in Surgery (STARSurg) network is a novel student-led, national research collaborative. Student collaborators contribute data to national, clinical studies while gaining an understanding of audit and research methodology and ethical principles. This study aimed to evaluate the educational impact of participation. METHODS: Participation in the national, clinical project was supported with training interventions, including an academic training day, an online e-learning module, weekly discussion forums and YouTube® educational videos. A non-mandatory, online questionnaire assessed collaborators’ self-reported confidence in performing key academic skills and their perceptions of audit and research prior to and following participation. RESULTS: The group completed its first national clinical study (“STARSurgUK”) with 273 student collaborators across 109 hospital centres. Ninety-seven paired pre- and post-study participation responses (35.5%) were received (male = 51.5%; median age = 23). Participation led to increased confidence in key academic domains including: communication with local research governance bodies (p < 0.001), approaching clinical staff to initiate local collaboration (p < 0.001), data collection in a clinical setting (p < 0.001) and presentation of scientific results (p < 0.013). Collaborators also reported an increased appreciation of research, audit and study design (p < 0.001). CONCLUSIONS: Engagement with the STARSurg network empowered students to participate in a national clinical study, which increased their confidence and appreciation of academic principles and skills. Encouraging active participation in collaborative, student-led, national studies offers a novel approach for delivering essential academic training. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12909-015-0326-1) contains supplementary material, which is available to authorized users.